Detection of Ehrlichia spp. in the Blood of Wild White-Tailed Deer in Missouri by PCR Assay and Serologic Analysis - Arens, Max Q.; Liddell, Allison M.; Buening, Gerald; Gaudreault-Keener, Monique; Sumner, John W.; Comer, James A.; Buller, Richard S.; Storch, Gregory A. (Journal of Clinical Microbiology, 2003)
Article Usage Stats Services JCM Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue JCM About JCM Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JCM RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0095-1137 Online ISSN: 1098-660X Copyright © 2014 by the American Society for Microbiology. For an alternate route to JCM .asm.org, visit: JCM